Publisher Correction: Endothelial progeria induces adipose tissue senescence and impairs insulin sensitivity through senescence associated secretory phenotype - Agian Jeffilano Barinda (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.